Techniques for Imaging Vascular Supply of Peripheral Nerves - Giron, Alec; Cox, Cameron; MacKay, Brendan (Journal of Brachial Plexus and Peripheral Nerve Injury, 2021)
Few studies have been developed to map the vascular structures feeding peripheral nerves, with the majority using cadaveric models and inadequate sample sizes. Preliminary evidence, while limited, indicates that the mapping of these vessels may allow or preclude certain procedures in nerve reconstruction due to the location of essential arterial inflow to the vasa nervorum. This review evaluates the evidence regarding historical, current, and emerging techniques for visualizing these vascular structures in vivo and considers their potential application in peripheral nerve vasculature.
Keywords: imaging; peripheral nerve repair; CT imaging; ultrasound; peripheral vasculature; MRI; CEMRI; surgery